The portrayal of Australian women in property publications. Issue 1 (19th February 2018) - Antoniades, Hera; Warren, Clive M.J.
Abstract : Purpose: The purpose of this paper is to undertake an analysis of the visual portrayal of women published in a professional journal within the built environment and to establish whether or not there is gender stereotyping through these published images. Design/methodology/approach: A prominent property professional industry journal was selected for the research analysis. This journal was selected because of the national coverage within Australia and high prominence within the property industry. The analysis focused on a total of 166 pictures in the 2015 issues. The coding identified the publication year, issue number and page number of each photograph analysed and total number of pictures on each page. After this information was tabulated, each photograph was analysed using a thematic analysis approach. Findings: The research identified that given the opportunity to be photographed ad hoc, women tend to take the dominant stance and yet when the pictures were posed, the women showed a tendency to adopt a submissive stance. Male images were 13.39 per cent in the dominance category indicating a higher score in comparison to females at 3.45 per cent. Practical implications: Whilst it is generally accepted that there are more males in the built environment, the reality leans towards the notion that with less woman on property boards and management roles, it will be difficult to portray women in positions of authority and to balance the gender portrayal. In summary, the marginalisation of women is evident, and marketing media can be highly influential and unintentionally promote gender inequity with image portrayal. Originality/value: This research provides a valuable insight on how women are portrayed in the property profession. The property industry and the professional bodies can provide an influential role to promote gender equality.